Women's resistance portrayed in Toni Morrison's novel : beloved, the bluest eye and sula - Shiriya, Moon Moon (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2013.